2012
DOI: 10.1021/bm300310f
|View full text |Cite
|
Sign up to set email alerts
|

Polymer Composites Reinforced by Locking-In a Liquid-Crystalline Assembly of Cellulose Nanocrystallites

Abstract: An attempt was made to synthesize novel composites comprising poly(2-hydroxyethyl methacrylate) (PHEMA) and cellulose nanocrystallites (CNC) (acid-treated cotton microfibrils) from suspensions of CNC in an aqueous 2-hydroxyethyl methacrylate (HEMA) monomer solution. The starting suspensions (∼5 wt % CNC) separated into an isotropic upper phase and an anisotropic bottom one in the course of quiescent standing. By way of polymerization of HEMA in different phase situations of the suspensions, we obtained films o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
76
0
4

Year Published

2015
2015
2018
2018

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 84 publications
(84 citation statements)
references
References 13 publications
4
76
0
4
Order By: Relevance
“…The procedure for preparing the CNC used in this work was essentially the same as that described previously (Tatsumi et al 2012). In brief, CNC particles were isolated from cotton cellulose powder (Whatman, CF11) by acid hydrolysis with 65 wt% sulfuric acid, with mechanical stirring at 70°C for 15 min.…”
Section: Preparation Of Cncmentioning
confidence: 99%
See 1 more Smart Citation
“…The procedure for preparing the CNC used in this work was essentially the same as that described previously (Tatsumi et al 2012). In brief, CNC particles were isolated from cotton cellulose powder (Whatman, CF11) by acid hydrolysis with 65 wt% sulfuric acid, with mechanical stirring at 70°C for 15 min.…”
Section: Preparation Of Cncmentioning
confidence: 99%
“…3b. This morphology is apparently like the banded structure characteristic of shear-deformed polymer liquid crystals (Navard 1987;Nishio et al 1985), but, rather, it may be regarded as the trace of a helical arrangement of CNCs (Majoinen et al 2012;Tatsumi et al 2012); viz., the chiral nematic structure could develop in the process of condensation of the sheared suspension and partly remain in the dry sample, as discussed below. Another attention should be paid to the fact that no trace of such a mesomorphic organization was observed in the CNC-6.7 film.…”
Section: Microscopic Observations Of Cnc Filmsmentioning
confidence: 99%
“…In many cases, CNCs were compounded with thermoplastic polymers by simple mechanical mixing. As another route to microcomposition of CNCs, Tatsumi et al demonstrated a successful synthesis of polymer composites containing a fixed liquid crystalline arrangement of CNCs via bulk polymerization of monomer solvent [120]. From phase-separated suspensions of cotton CNCs in an aqueous 2-hydroxyethyl methacrylate (HEMA) monomer solution (water to HEMA ratio was 0.5-1.2:1 by volume), polymer composites PHEMA-CNC iso and PHEMA-CNC aniso coming from the upper isotropic phase and the lower anisotropic phase, respectively, were prepared in film form by photopolymerization of HEMA followed by oven-curing and drying.…”
Section: Polymer Composites With Liquid Crystalline Cncsmentioning
confidence: 99%
“…An extensive effort was made to synthesize further novel composites from similar CNC suspensions in water/monomer using a magnetic alignment [120] with an adequate modification) technique [123]. As shown in Fig.…”
Section: Polymer Composites With Liquid Crystalline Cncsmentioning
confidence: 99%
“…34,35 For instance, the Yamazaki group 36 used tungsten methylcellulose composite films as photochromic material.…”
mentioning
confidence: 99%